Intensification of traditional land use system :a case study at Kampung Long Pasia, Sabah - Sinimis Angelica Suimin., Suimin. (Faculty of Social Sciences, 2002)
Land resource is one of the most important aspects,in any agricultural developement. The scarcity of land resource may also affect agricultural development in the rural areas. The focus of this study is to evaluate and identify the intensification process of traditional land use in Long Pasia, Sabah, its constraints and prospects; its causal relationships with other rural develoment activities and its socio-economic impact on the livelihood of the people. The study also evaluates the existing traditional land use structure and social sustainability of resource allocation. In addition this study also serves to identify the level of household participation in land use intensification process and to highlight the application of indigenous resource management.